Ideas can bring new wonders - Abd Razak, Dzulkifli (2007)
PRESIDENT Fidel Castro recounted in a recent article his experience when he was about to be arrested by a lieutenant of the then president, General Fulgencio Batista. As the soldiers took aim at Castro, the patrol leader named Sarria said: "Ideas cannot be killed." He kept on repeating that ideas cannot be killed, presumably in reference to the futility of killing Fidel just because they hated his ideas. This was on July 26,1953 when at the age of 26, Castro led a group of 160 to attack the Moncada garrison in Santiago de Cuba, at the southern part of the island.